2023
DOI: 10.3390/cimb45050251
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evaluation of the Impact of Polymorphic Variants in Apoptotic (Bcl-2/Bax) and Proinflammatory Cytokine (TNF-α/IL-8) Genes on the Susceptibility and Progression of Myeloproliferative Neoplasms: A Case-Control Biomarker Study

Abstract: The regulation of apoptosis (the programmed cell death) is dependent on the crucial involvement of BCL2 and BAX. The Bax-248G>A and Bcl-2-938 C>A polymorphic variations in the promoter sequences of the Bax and Bcl-2 gene have been recently associated with low Bax expression, progression to advanced stages, treatment resistance, and shortened overall survival rate in some hematological malignancies, including chronic myeloid leukemia (CML) and other myeloproliferative neoplasms. Chronic inflammation has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Hence, this gene is considered to be an important suppressor of hematopoietic malignancies [34]. In the case of polycythemia vera or essential thrombocythemia, there was no significant difference in the frequency of genotypes for the BAX −248G>A (rs4645878) polymorphism between the patients and the control group [33]. Our analysis of BAX (rs4645878, G>A) and c-MYC (rs13281615, A>G) polymorphisms also showed no association with ovarian cancer risk.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Hence, this gene is considered to be an important suppressor of hematopoietic malignancies [34]. In the case of polycythemia vera or essential thrombocythemia, there was no significant difference in the frequency of genotypes for the BAX −248G>A (rs4645878) polymorphism between the patients and the control group [33]. Our analysis of BAX (rs4645878, G>A) and c-MYC (rs13281615, A>G) polymorphisms also showed no association with ovarian cancer risk.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, some polymorphisms, such as BAX −248G>A (rs4645878) and BCL2 −938C>A (rs2279115), have been determined to exhibit changes in gene expression contributing to diseases [33]. It has been shown that deletions of the BAX gene may be associated with the occurrence of lymphoid hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…All the above-mentioned findings highlight the importance of ANKRD36 in pivotal biological functions and its notable association with cancer progression in CML patients. Moreover, the identification of ANKRd36 mutations exclusively with AP-/BC-CML suggests that it is a novel molecular biomarker that can be used to monitor CML progression, early determination of patients at risk of CML progression, particularly blast crisis, and carry out timely therapeutic interventions of at-risk patients to delay or minimize blast crisis development, that can lead to considerable improvement in overall survival of high risk BC-CML patients (30). Given its highest expression in myeloid cells of the bone marrow, ANKRD36 holds potential as a potential novel drug target, particularly for patients with advanced phases of CML (13,31).…”
Section: Discussionmentioning
confidence: 99%